The formation of a creative personality through the system of physical education and healthy lifestyle of the future teachers - Андріанов, Вадим Євстафійович; Андріанов, Тарас Вадимович (Pedagogy of Higher and Secondary Education, 2016)
Andrianov V. Ye. , Andrianov T. V. The formation of a creative personality through the system of physical education and healthy lifestyle of the future teachers. The article defines peculiarities of the formation of habits for a healthy lifestyle as an integral component of formation of a creative personality of the future teacher in the system of physical education. The attention is focused on the importance of application of active forms of education in physical training classes.